PENGARUH PERPUTARAN PIUTANG, PERSEDIAAN DAN SKALA PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAN PROPERTY - Ruhmana, Futikha Dewi; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTProfitability is the ability of the company to gain profit in relation to the total assets sales or own capital with the primary objectives is corporate profit. The purpose of this research is to find out the influence of account receivable turnover, inventory turnover and firm scale to the profitability of property companies which are listed in Indonesia Stock Exchange. The population of this research are companies which are engaged in the property which are listed in Indonesia Stock Exchange in 2010-2015 periods. The data is the secondary data in the form of financial statements. The analysis instrument is the multiple linear regression analysis. It has been found from the result of the research that account receivable turnover give positif significant influence to the profitability. Meanwhile, inventory turnover and firm scale does not give significant influence to the profitability. On simultaneous test, account receivable turnover, inventory turnover and firm scale give significant influence to the profitability. The R Square value in the regression model has obtained is 0.812. It means that the influence of account receivable turnover, inventory turnover and firm scale to the profitability which can be generated from this equation is 81% and the remaining 19% can be explained by other variables.Keywords: Account receivable turnover, inventory turnover, firm scale